Peranan Pajak Hotel Dan Restoran Terhadap Pembangunan Daerah Kota Medan - M. Ridho Al aziz; Muhammad Irwan Padli Nasution (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Development is a very important thing to do in every region, including the source of regional development funds, namely the role of hotel taxes and restaurant taxes. Infrastructure is the most strategic infrastructure in the development process of a region, influencing economic activities and providing various other infrastructure. Inefficient development can cause socioeconomic decline and social adequacy. Regional taxes function as development funds, including road infrastructure. Independence and original regional income influence and help ensure that regional income is good for managing regional households and improving the regional economy. One of the drivers of development in the city of Medan is hotel and restaurant taxes, therefore the author really wants to research more deeply regarding the extent to which regional development has been optimized from hotel and restaurant taxes.